The impact of exogenous shocks on exchange rates in Vietnam - Mai Chi, Vu; Khanh, Pham; Phu Dong, Do (Edelweiss Applied Science and Technology, 2024)
This paper investigates how exogenous shocks, including inflation, interest rates, energy prices, and crisis factors, are transmitted to the exchange rate and subsequently impact the economy. The transmission process is analyzed through the lens of the SBV's exchange rate management responses. Furthermore, the objective of this study is to evaluate the capacity of Vietnamese exchange rate system to sustain shocks. The article measures the effect of non-systematic shocks using a Dummy variable, where 0 represents normal conditions and 1 represents the time when shocks occur with the use of the monthly data from January 2009 to December 2022, compiled from data sources of the State Bank, GSO, IMF, and WB. The results show that the trend of exogenous shocks in the market over the past time is relatively favorable for exchange rate management in Vietnam, when the transmission reaction from market supply-demand shocks has a limited impact on the exchange rate and inflation. However, as the domestic economy and finance become more and more deeply integrated with the world, exogenous shocks may have a stronger impact. These findings have important policy implications for improving the SBV’s exchange rate management efficiency in relation to other variables to optimize the achieved target.